Penerapan Reliability Centered Maintenance dalam meningkatkan kinerja mesin sewing - Handra, Valencia Febrianti; Hadisantono; Hanandoko, Theodorus B. (Jurnal Teknik Industri dan Manajemen Rekayasa, 2025)
[Design of a Maintenance System to Reduce the Frequency of Sewing Machine Component Failures] PT Jogja Glove Indonesia is a manufacturing company engaged in glove production. During its production process, the company faces frequent sewing machine breakdowns, which lead to increased downtime and hinder the achievement of the daily production target of 1,000 pieces. This condition reduces production line efficiency and may disrupt the company’s ability to meet customer demand. This study aims to identify the root causes of frequent sewing machine failures and to formulate systematic improvement solutions. The research method adopts the Design Thinking approach, which consists of five stages: Empathize, Define, Ideate, Prototype, and Test. Data were collected through field observations, interviews with operators and technicians, and analysis of machine downtime records. The Reliability Centered Maintenance (RCM) approach was implemented through FMEA analysis, MTTR and MTTF calculations, and the development of preventive maintenance Standard Operating Procedures (SOP). The results show a 54.1% reduction in machine failure frequency, from an average of 368 to 169 incidents per month. Additionally, pass products increased by 37.73%, while rejects decreased by 36.46%. In conclusion, the implementation of RCM-based preventive maintenance proved effective in improving sewing machine reliability, operational efficiency, and production quality.